2016
DOI: 10.1684/ecn.2016.0382
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 functional polymorphisms: a review

Abstract: Transforming Growth Factor ß (TGF-ß) is a multifunctional cytokine that plays a role in several biological processes. TGF-ß1 is the most abundantly expressed isoform, associated with susceptibility to various diseases, and several polymorphisms have been described in the TGF-ß1 gene structure, and some of them have been associated with functional implications. To date, eight single-nucleotide polymorphisms (SNPs) and one deletion/insertion polymorphism have been shown to affect TGF-ß1 expression (rs2317130, rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 98 publications
0
52
1
1
Order By: Relevance
“…This SNP (Single Nucleotide Polymorphism) is located in a region encoding the hydrophobic core of the TGF-β1 signal peptide and results in a substitution of proline with leucine in the 10th position of the amino acid sequence. The c.+29C results in increased TGF-β1 secretion in vitro and in vivo compared with c.+29T [178]. Chen et al found Int7G24A (rs334354) intronic variant of the TGFBR1 gene frequently associates with transitional cell carcinoma (TCC) of the bladder as well as renal cell carcinoma [141].…”
Section: Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This SNP (Single Nucleotide Polymorphism) is located in a region encoding the hydrophobic core of the TGF-β1 signal peptide and results in a substitution of proline with leucine in the 10th position of the amino acid sequence. The c.+29C results in increased TGF-β1 secretion in vitro and in vivo compared with c.+29T [178]. Chen et al found Int7G24A (rs334354) intronic variant of the TGFBR1 gene frequently associates with transitional cell carcinoma (TCC) of the bladder as well as renal cell carcinoma [141].…”
Section: Bladder Cancermentioning
confidence: 99%
“…Specifically, homozygotic TT patients had a lower risk of recurrence following BCG treatment [341]. Interestingly, this genotype is associated with increased TGF-β expression when compared with CC homozygotes, and individuals with T substitution have twice higher TGF-β1 plasma concentrations when compared with CC carriers [174,178]. TGF-β modulates the functioning of myeloid-derived suppressor cells (MDSCs) of bladder cancer patients.…”
Section: Tgf-β1 and Micrornas And Treatment Of Gcmentioning
confidence: 99%
“…Both tumorigenic and tumor-suppressive roles of TGF-β1 have been well established [5]. Elevated plasma levels of TGF-β1 have been associated with cancer development, and TGF-β1 polymorphisms have been found to cause high transcription and expression of TGF-β1 [9,11]. The prominent role of TGF-β1 in cancer progression underscores the importance of studying the association between TGF-β1 polymorphisms and BC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several polymorphisms have been identified in the TGF-β1 gene (TGFβ1), including two located in exon 1 (TGF-β1 29T>C and TGF-β1*6A) and two located in the promoter region (TGF-β1-509 C/T and TGF-β1-800 G/A) [8][9][10]. There is increasing evidence of an association between these polymorphisms and elevated cancer risk [11]. Researchers demonstrated that the TGF-β1 29T>C polymorphism increases the secretion of TGF-β levels [9].…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor-β (TGF-β) is a multifunctional cytokine that regulates cell growth and differentiation, as well as regulates cell proliferation through the TGF-β/Smad signaling pathway (Martelossi Cebinelli, Paiva, Badaró, et al, 2016). TGF-β/Smad signaling dysregulation has been frequently observed in various types of cancers (Kaminska, Wesolowska, & Danilkiewicz, 2016).…”
mentioning
confidence: 99%